Language and ideology: semiologic transformation - Kıraç, Ziya Kıvanç (My University, 2023)
Human beings are born with language skills. However, the development of language is a result of human sociality and culture. Language is transmitted both vertically from generation to generation and horizontally between people. It is assumed that what cannot be expressed in language is not real. Therefore, meaning is only possible within the boundaries of a language. Through meaning, everything that happens becomes conceptualized and standardized. Language shows the meaning of reality through signs. In this way, language goes beyond being a means of communication. It becomes a tool of power struggle. Identifying and revealing the ideological influence in language necessitates different linguistic methods. Because by their very nature, signs transmit an infinite number of complex connections. Ideology, presented as a way of thinking correctly, establishes social relations and directs social action through signs. In this sense, signs are key concepts in the reproduction of ideology. On the other hand, the symbol, which is considered a sign, serves a different dimension of ideology. Symbols also convey meaning. However, their arbitrary construction takes ideology out of the definition of the reproduction of power It gives ideology a dimension such as a mass movement, a grand narrative. Providing meaning to the masses and being a guide is a feature that ideologies establish with symbols. The aim of this study is to explain the possible links between reality, knowledge and ideology based on the distinctions between sign and symbol. In this way, a distinction is made between old-style knowledge and modern knowledge.
Keywords: Knowledge; Ideology; Language; Symbol; Sign; Semiology